Measuring Uncertainty of a Combined Forecast and Some Tests for Forecaster Heterogeneity - Kajal Lahiri; Huaming Peng; Xuguang Sheng (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We have argued that from the standpoint of a policy maker who has access to a number of expert forecasts, the uncertainty of a combined forecast should be interpreted as that of a typical forecaster randomly drawn from the pool. With a standard factor decomposition of a panel of forecasts, we show that the uncertainty of a typical forecaster can be expressed as the disagreement among the forecasters plus the volatility of the common shock. Using new statistics to test for the homogeneity of idiosyncratic errors under the joint limits with both T and n approaching infinity simultaneously, we find that some previously used measures significantly underestimate the conceptually correct benchmark forecast uncertainty.
Keywords: C12; C33; E37; 330; disagreement; forecast combination; panel data; uncertainty